2016
DOI: 10.4274/tdd.3038
|View full text |Cite
|
Sign up to set email alerts
|

Ticks, Borrelia Burgdorferi and Lyme Disease

Abstract: Lyme disease, which is caused by spirochete Borrelia burgdorferi sensu lato, is a ticktransmitted, multisystem infectious disease. It occurs in stages, with different clinical manifestations at each stage. Erythema migrans is the most frequent manifestation which occurs at the site of the tick bite. Borrelial lymphocytoma and acrodermatitis chronica atrophicans are late-stage cutaneous manifestations. Extracutaneous signs of infection most often involve the musculoskeletal, cardiovascular, and nervous systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In our study, there were 21 early-phase Lb patients with the tick staying in the skin for only 10 hours or up to one day who developed changes in the central and peripheral nervous systems, which is in agreement with some authors, but also in contradiction with some others [2,3,25,26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, there were 21 early-phase Lb patients with the tick staying in the skin for only 10 hours or up to one day who developed changes in the central and peripheral nervous systems, which is in agreement with some authors, but also in contradiction with some others [2,3,25,26].…”
Section: Discussionsupporting
confidence: 91%
“…Ixodes ricinus has been proved to be a vector in our country. The infection occurs after one to three days, and rarely within 24 hours, due to inappropriate tick removal [2,3]. The risk of developing Lyme disease after the bite of an infected tick is 1-4%, while asymptomatic infections range up to 26% in the endemic area [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Largely due to the prevalence of infectious diseases and limitations to current medical sciences, vaccine fatigue may be difficult to avoid in certain circumstances. Our findings show that many antecedents of vaccine fatigue are rooted in flaws in vaccine sciences, such as adverse effects caused by vaccination ( 28 , 29 , 31 , 39 , 44 ), poor vaccine efficacy ( 21 , 22 , 49 ), as well as too many vaccination demands in a relatively short period of time ( 34 , 50 , 56 , 60 ). A study on people who received the BioNTech-Pfizer doses, for instance, found that 83.3% of the vaccine recipients experienced post-vaccination fatigue ( 28 ).…”
Section: Discussionmentioning
confidence: 83%